2018
DOI: 10.1007/s00438-018-1423-8
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein Rbpms is represented in human retinas by isoforms A and C and its transcriptional regulation involves Sp1-binding site

Abstract: Rbpms (RNA-binding protein with multiple splicing) is a member of the RRM (RNA Recognition Motif) family of RNA-binding proteins, which is expressed as multiple alternatively spliced transcripts encoding different protein isoforms. We have shown earlier that Rbpms expression in the retina is restricted to retinal ganglion cells (RGCs), and have characterized this gene as a marker for RGCs. The aim of this study was to identify isoforms representing Rbpms in human retinas and to analyze its transcriptional regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Some promoters known to express specifically in RGCs have either not been expressed highly or are too large to be included in AAV vectors, which have a maximum cargo capacity of approximately 4.7 kb, e.g. Brn3a, Thy1 and Rbpms [8][9][10][11][12][13] . Notably, the size of both the human NEFH promoter (2.5 kb) and, particularly, the truncated hA-P promoter (199 bp) are ideal for application within AAV vectors and thereby represents a significant advantage over the larger RGC promoters published to date 6,[14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some promoters known to express specifically in RGCs have either not been expressed highly or are too large to be included in AAV vectors, which have a maximum cargo capacity of approximately 4.7 kb, e.g. Brn3a, Thy1 and Rbpms [8][9][10][11][12][13] . Notably, the size of both the human NEFH promoter (2.5 kb) and, particularly, the truncated hA-P promoter (199 bp) are ideal for application within AAV vectors and thereby represents a significant advantage over the larger RGC promoters published to date 6,[14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, many promoter sequences of genes known to be RGC-specific, such as Brn3a , Thy1 and Rbpms , are too large to be incorporated into AAV vectors, the vector of choice for many ocular gene therapies. AAV has a maximum cargo capacity of approximately 4.7 kb 8 13 . One study demonstrated that the DCX promoter (3310 bp; doublecortin) can drive strong and specific RGC expression following AAV-QuadYF-mediated delivery 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Third, the hES-VSMC model explores the splicing activity of a single isoform – RBPMS-A, overexpressed at non-physiological levels (Fig 4 associated supplementary C). RBPMS, (by virtue of its own splicing), is physiologically expressed as multiple transcript isoforms with at least 2 main (A and B) protein isoforms that we have observed to possess differential activity [7, 60]. To compound this, RBPMS activity is also regulated by post-translational modifications [61].…”
Section: Discussionmentioning
confidence: 99%
“…The following primary antibodies were used: mouse anti-GFP (1:200; Millipore, MAB#3580); goat anti-GFP (1:200; Rockland Inc., 600-101-215); rabbit anti-GFP (1:200; Rockland Inc., 400-401-215); mouse anti-FLAG (Clone M2) (1:500; Sigma-Aldrich, F3165); rabbit anti-ATOH7 (1:100; NovusBio, NBP1-88639); goat anti-Ngn2 (1:200; Santa Cruz Biotechnology, sc-19233); mouse anti-BrdU (1:1; GE Healthcare, RPN202); mouse anti-PCNA (1:500; Sigma-Aldrich, P3825); rabbit anti-phospho-histone 3 (ser10) (1:3,000; Upstate Biotechnology, 06-570); rabbit anti-Pax6 (1:200; Chemicon, ab5409); goat anti-CHX10/VSX2 (N-18) (1:50; Santa Cruz Biotechnology, sc-21690); goat anti-BRN3a (1:100; Santa Cruz Biotechnology, sc-31984); goat anti-pan BRN3 (1:50; Santa Cruz Biotechnology, sc-6026); mouse anti-Iselt1 (1:10; Developmental Study Hybridoma Bank, 39.4D5); mouse anti-doublecortin (E-6) (1:50; Santa Cruz Biotechnology, sc-271390); rabbit anti-NeuN (1:200; Abcam, ab177487); rabbit anti-NF145 (1:750; Millipore, AB1987); rabbit anti-RBPMS (1:200; Ye et al, 2018 ). Secondary antibodies used were: Alexa Fluor 488 donkey anti-mouse (1:500; Thermo Fisher, A32766); Alexa Fluor 488 donkey anti-rabbit (1:500; Thermo Fisher, A32790); Alexa Fluor 488 donkey anti-goat (1:500; Thermo Fisher, A32814); Alexa Fluor 594 donkey anti-mouse (1:500; Thermo Fisher, A32744); Alexa Fluor 594 donkey anti-rabbit (1:500; Thermo Fisher, A32754); Alexa Fluor 594 donkey anti-goat (1:500; Thermo Fisher, A32758); Alexa Fluor 647 donkey anti-mouse (1:500; Thermo Fisher, A32787); Alexa Fluor 647 donkey anti-rabbit (1:500; Thermo Fisher, A32795); Alexa Fluor 647 donkey anti-goat (1:500; Thermo Fisher, A32849).…”
Section: Methodsmentioning
confidence: 99%